Patient Engagement at a Tipping Point—The Need for Cultural Change Across Patient, Sponsor, and Regulator Stakeholders: Insights From the DIA Conference, "Patient Engagement in Benefit Risk Assessment Throughout the Life Cycle of Medical Products". (September 2016) - Smith, Meredith Y.; Hammad, Tarek A.; Metcalf, Marilyn; Levitan, Bennett; Noel, Rebecca; Wolka, Anne M.; Michaels, Debra L.; Johnson, F. Reed
Benefit-risk assessment is the foundation for decision making throughout the life cycle of medical products. Because patients are the beneficiaries of the efficacy of medical treatments and also bear their possible risks, their perspectives and judgments about value and the relative importance of benefits and risks should be at the heart of the medical decision-making process. Patient engagement is now at a tipping point; there have been a growing number of patient engagement initiatives over the past several years, but there remains the need for a common language, alignment on engagement approaches and best practices, and a shared vision regarding a desired future state. This article discusses insights gleaned from the DIA conference, "Patient Engagement in Benefit-Risk Assessment throughout the Life Cycle of Medical Products" (September 2015). It highlights the changes that will need to occur within the patient, medical-product sponsor, and regulatory cultures in order for patient engagement to become integrated into the medical-product development process and life cycle maintenance. Furthermore, it emphasizes that reaching the desired future state will require a conscious commitment from all stakeholders to work collaboratively to develop shared solutions and to map a common path forward.